Silk Road Revival: Language Contact and Cross-Cultural Communication in the China-Pakistan Economic Corridor - Khan, Muhammad Ijaz; Hanzala; Huraira, Abu (Annals of Human and Social Sciences, 2024)
The study aims to explore the linguistic meaning that has arisen, along with international trade and investment, because of CPEC (China-Pakistan Economic Corridor), and in so doing perhaps stimulate language contact coordination across multiethnic regions on either side. To conduct this qualitative research, thematic way was followed. In which already published research papers were selected by using purposive-sampling method. A systematic thematic analysis of the chosen articles show that CPEC assumes a substantial linguistic role in international trade, with English and Mandarin emerging as the predominant languages employed. This research concludes that linguistic variety, far from being a liability or burden, is an asset worth nurturing which can generate cross-cultural communication and understanding as well as adaptability. This study recommends extending beyond Pakistan's borders, offering a model for linguistically diverse regions in global trade, aiming to maximize language diversity for economic progress and intercultural cooperation.